PRE-MARRIAGE AND YOUNG MARRIAGE COUNSELING IN KERINCI - Arrahman, Iqbal; Firman, Firman; Mohamed Sidik, Mohd Suhadi (Consilium: Education and Counseling Journal, 2024)
Nowadays, Allah SWT has mandated marriage as sunnatullah. According to Maqashid sharia, marriage has a very noble purpose, namely caring for or raising children. Early marriage or early marriage is still a controversial issue that is often discussed by many people, but this goal can be achieved if its implementation is in line with the guidelines set by Allah SWT as the Lord who creates and makes rules so that humanity remains of noble character. . There are those who consider this beneficial because, in some cases, religiously it can prevent the younger generation from committing adultery. The economy is a factor in another explanation. In an effort to give their daughters a better life after marriage, some parents decide to marry off their young daughters to adult men who have steady jobs. in Kerinci Regency. The prospective wife is between 14 and 16 years old, and the prospective husband is between 16 and 20 years old. The person is still considered a teenager at that age. Children are still not emotionally stable during adolescence, so they easily make quick decisions. Young marriages between teenagers who have not completed their developmental tasks can cause conflict because the newlyweds are not ready to assume responsibility and carry out their roles as husband and wife. Teenagers who are thinking about getting married should receive premarital counseling from the Sangha. Premarital counseling is the quick delivery of information, understanding and practical skills related to domestic life to prospective husbands and wives. Therefore, premarital counseling refers to information or education provided regarding the various nuances of marriage before the implementation of the marriage contract. A literature review regarding premarital counseling and young marriages in Kerinci was used to implement this research design.